Screening versions of the European Portuguese MacArthur-Bates Communicative Development Inventories Short Forms: development and preliminary validation - Filipe, Marisa G.; Severino, Cátia; Vigário, Marina; Frota, Sónia (Frontiers in Psychology, 2025)
This study aimed to develop and validate the screening versions of the European Portuguese MacArthur-Bates Communicative Development Inventories Short Forms (EP CDI-SFs), intended to guide referrals for comprehensive language assessments in infants and toddlers. The first cohort, aged 8–18 months, included 1,293 typically developing children (Mage = 12.23, SD = 3.12, 50.2% male), 170 children at-risk for language impairments (Mage = 11.76, SD = 2.81, 45.9% male), and 39 children with Down syndrome (Mage = 12.28, SD = 3.40, 56.4% male), assessed using the EP CDI-SF Level I. The second cohort, aged 16–30 months, included 1,155 typically developing children (Mage = 23.45, SD = 4.07, 51.2% male), 181 children at-risk for language impairments (Mage = 23.23, SD = 4.31, 47% male), and 46 children with Down syndrome (Mage = 23.09, SD = 3.93, 69.6% male), assessed with the EP CDI-SF Level II. Through factor analysis, the 20 most psychometrically robust items from each form were identified and used to develop the new screening versions (EP CDI-Scr). Strong correlations between the EP CDI-SFs and EP CDI-Scr results for typically developing children, along with excellent internal consistency, supported the validity and reliability of the new tools. Furthermore, the EP CDI-Scr versions demonstrated excellent sensitivity and moderate specificity. They effectively distinguished between typically developing children, those at-risk for language impairments, and those with Down syndrome, confirming strong discriminant validity. These findings establish the preliminary validity, reliability, and effectiveness of the EP CDI-Scr, supporting timely referrals for comprehensive language evaluations.